A Static Facial Sling Technique Restoring Nasolabial Sulcus in Facial Paralysis. Issue 4 (June 2019) - Dornhoffer, James; Vural, Emre
Abstract : Abstract: Static facial sling techniques are useful rehabilitation modalities where dynamic rehabilitation methods are not feasible in the management of facial paralysis. The authors present their technique as an alternative static sling method, which may give the patient a more natural nasolabial sulcus restoration in addition to suspension of the oral commisure.